2021
DOI: 10.1111/1460-6984.12644
|View full text |Cite
|
Sign up to set email alerts
|

Oral and written communication skills of adolescents with prenatal alcohol exposure (PAE) compared with those with no/low PAE: A systematic review

Abstract: Background: Prenatal alcohol exposure (PAE) is associated with growth deficits and neurodevelopmental impairment including foetal alcohol spectrum disorder (FASD). Difficulties with oral and written communication skills are common among children with PAE; however, less is known about how communication skills of adolescents who have PAE compare with those who do not. Adolescence is a critical time for development, supporting the transition into adulthood, but it is considered a high-risk period for those with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…sleep, face structure, hearing), developmental delays in early childhood and general health challenges. These indicators had significantly less evidence but were examined in adult and youth corrections as well as a programme for legally involved adults, through multiple methods, including record reviews (Russell et al., 2021), completion of tasks/checklists (Kippin et al., 2021), SRT ratings (Conry & Asante, 2010), and interviews (Kippin et al., 2018). Sleep disturbances were a common physical health challenge for youth with FASD (35.9%; Russell et al., 2021), as was a history of recurring ear infections for youth in detention (28.0%; Kippin et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…sleep, face structure, hearing), developmental delays in early childhood and general health challenges. These indicators had significantly less evidence but were examined in adult and youth corrections as well as a programme for legally involved adults, through multiple methods, including record reviews (Russell et al., 2021), completion of tasks/checklists (Kippin et al., 2021), SRT ratings (Conry & Asante, 2010), and interviews (Kippin et al., 2018). Sleep disturbances were a common physical health challenge for youth with FASD (35.9%; Russell et al., 2021), as was a history of recurring ear infections for youth in detention (28.0%; Kippin et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kippin et al. (2021) found that adolescents with PAE presented with features consistent with malocclusions at high rates (18.0%). Developmental delay was an item on the SRT that distinguished youth at risk and not at risk for FASD (Conry & Asante, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptive vocabulary refers to the words an individual can assign meanings to while listening or reading. (Kippin et al, 2021). Productive vocabulary is the set of words that a person can use when writing or speaking (Morente et al, 2022).…”
Section: The Concept Of Vocabularymentioning
confidence: 99%
“…As a result, it is unclear how the grammatical skills of adolescents with PAE compare to those of those without PAE or with low PAE, and what the implications are for their communication skills. [11] The issue is still not fully explored.…”
Section: The Impact Of Pae On the Onset Of Speech Disorders And Commu...mentioning
confidence: 99%